LINC00202 promotes retinoblastoma progression by regulating cell proliferation, apoptosis, and aerobic glycolysis through miR-204-5p/HMGCR axis - Wu, Aimin (Open Life Sci, 2020)
LINC00202 is a newly identified long noncoding RNA (lncRNA) and has been demonstrated to involve in the progression of retinoblastoma (RB). Here, we further explored the role and the underlying molecular mechanism of LINC00202 on RB malignant properties and glycolysis. LINC00202, microRNA (miR)-204-5p, and 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR) mRNA were detected by a quantitative real-time polymerase chain reaction. Cell proliferation and apoptosis were analyzed using cell counting kit-8 assay and colony formation assay and flow cytometry, respectively. Glucose metabolism was calculated by measuring the extracellular acidification rate (ECRA). Western blot was used to detect the levels of HMGCR, ki67, pro-caspase-3, cleaved-caspase-3, and lactate dehydrogenase A chain (LDHA). The interaction between miR-204-5p and LINC00202 or HMGCR was analyzed by the dual-luciferase reporter assay. Murine xenograft model was established to conduct in vivo experiments. LINC00202 expression was upregulated in RB tumor tissues and LINC00202 knockdown inhibited RB cell proliferation, glycolysis, and stimulated apoptosis in vitro as well as impeded tumor growth in vivo. MiR-204-5p directly bound to LINC00202 and HMGCR in RB cells, and LINC00202 functioned as a competing endogenous RNA in regulating HMGCR through competitively binding to miR-204-5p. More importantly, the regulation of malignant properties and glycolysis of RB cells mediated by LINC00202 could be reversed by abnormal miR-204-5p or HMGCR expression in RB cells. In all, LINC00202 promoted RB cell proliferation, glycolysis, and suppressed apoptosis by regulating the miR-204-5p/HMGCR axis, suggesting a novel therapeutic target for patients with RB.